SECURING THE BRITISH RECORDS ASSOCIATION'S LEGACY: CATALOGUING THE ASSOCIATION'S ARCHIVES AT THE LONDON METROPOLITAN ARCHIVES. Issue 1 (April 2020) - Baker, Penelope
Abstract : In April 2017, the British Records Association (BRA) moved to shared office space at Cowcross Street and closed its records storage and distribution service, which had been run by volunteers since 2008. This prompted the transfer of 'office' files, many of which dated back to the 1970s and beyond, to the London Metropolitan Archives (LMA). The BRA had deposited records with the LMA when the association vacated its space there in 2004 and the LMA received approximately 40 further boxes in six accessions from individual officers of the BRA. BRA volunteer Alison Cassidy, who had been helping with the final despatches of deposited records, has been working with Sally Bevan, senior archivist at the LMA, to list these uncatalogued 123 boxes, which doubles the extent of the BRA archives that will be available for research at the LMA. The existing catalogued records were also reviewed, and work is under way to produce an integrated catalogue. This article is a preliminary review of the BRA Archives at the LMA, which provide a fascinating picture of the evolution of the association, and the major role it has played in preserving and promoting the value of archives and records over the past 90 years.